Penggunaan Bahasa Indonesia di Kalangan Mahasiswa (Studi Kasus Mahasiswa Universitas Islam Negeri Sumatera Utara) - Edi Syahputra; Sabila Kamalia; Balqis Qonita Harahap; Novi Yanti; Fadlah Putri Sabila (Jurnal Multidisiplin Dehasen (MUDE), 2022)
In simple terms, language can be interpreted as a tool to communicate something. It came to my mind. In addition, language is also a tool or tool for interacting. Communicating in the sense of a tool for conveying thoughts, ideas, concepts, etc. In sociolinguistics, language is defined as a system of symbols, In sound form, it is arbitrary, productive, dynamic, diverse and human. Understanding language in the large Indonesian dictionary, understanding language in general can be interpreted as a symbol, the meaning of language after the term is a communication tool in the form of a symbol system produced by human speech. Language is also a part of culture, language that developed. Culture as we know it today. Language also acts as a tool of social integration and social adaptation which is considered Indonesian There are many languages.